A global perspective on the crosstalk between saturated fatty acids and Toll-like receptor 4 in the etiology of inflammation and insulin resistance. (January 2020) - Li, Bin; Leung, Joseph C.K.; Chan, Loretta Y.Y.; Yiu, Wai Han; Tang, Sydney C.W.
Abstract: Obesity is featured by chronic systemic low-grade inflammation that eventually contributes to the development of insulin resistance. Toll-like receptor 4 (TLR4) is an important mediator that triggers the innate immune response by activating inflammatory signaling cascades. Human, animal and cell culture studies identified saturated fatty acids (SFAs), the dominant non-esterified fatty acid (NEFA) in the circulation of obese subjects, as non-microbial agonists that trigger the inflammatory response via activating TLR4 signaling, which acts as an important causative link between fatty acid overload, chronic low-grade inflammation and the related metabolic aberrations. The interaction between SFAs and TLR4 may be modulated through the myeloid differentiation primary response gene 88-dependent and independent signaling pathway. Greater understanding of the crosstalk between dietary SFAs and TLR4 signaling in the pathogenesis of metabolic imbalance may facilitate the design of a more efficient pharmacological strategy to alleviate the risk of developing chronic diseases elicited in part by fatty acid overload. The current review discusses recent advances in the impact of crosstalk between SFAs and TLR4 on inflammation and insulin resistance in multiple cell types, tissues and organs in the context of metabolic dysregulation.